Answer:
x = 8
Step-by-step explanation:
Since m and n are parallel lines, then
6x - 2 = 46 ← alternate angles
Add 2 to both sides
6x = 48 ( divide both sides by 6 )
x = 8
Answer:
x=8
Step-by-step explanation:
The value of the angles are the same due to them being alternate interior angles and opposite angles. This means we can set 6x-2=46. Add 2 to each side to isolate the 6x. This leaves you with 6x=48. Divide by 6 to isolate x. 48/6= 8. X=8. Hope this helps :).
A 26 foot rope is used to brace a tent pole at the county fair. the rope is anchored 10 feet from the box of the pole. How tall is the pole? (answers above^^)
Using the Pythagorean theorem a^2 + b^2 = c^2 where a and b are the side and bottom of the triangle and c is the hypotenuse ( length of rope).
Let the tent pole = a
Lhe distance from the pole be b = 10 ft.
The length of rope would vce c = 26 ft.
Now you have:
a^2 + 10^2 = 26^2
Simplify:
a^2 + 100 = 676
Now subtract 100 from each side:
a^2 = 576
To get a, take the square root of both sides:
a = √576
a = 24
The tent pole is B. 24 ft
For Sophia's graduation party, several tables of the same width will be arranged end to end to form a serving table with a
total area of 75 ft. The total length of the tables will be two more than three times the width. Find the length and width of
the serving table so that Sophia can purchase the correct table cloth. Round your answers to the nearest tenth.
Area: 75 ft
Bw + 2
Answer:
Width=4.7 ft
Length=16.1 ft
Step-by-step explanation:
Let the width of the table to be x ft
Then the length should be two more than three times the width= 2+3x ft
The area of the serving table should be 75 ft²
But you know the area of this table is calculated by multiplying the length by the width of the table
Hence, Area= length× width
Length=x ft and width =2+3x ft
75ft²= (x ft) × (2+3x ft)
[tex]75=x*(2+3x)\\\\75=2x+3x^2\\\\3x^2+2x-75=0[/tex]
Apply the quadratic formula to solve this quadratic equation
The formula is ;
x= (-b ±√b²-4ac)÷2ac
where a=3, b=2 and c=-75
x= (-2 ± √2²-4×3×-75)÷(2×3)
x=(-2±√4+900)÷6
x=(-2±√904)÷6
x=(-2±30.1)÷6
x=(-2+30.1)÷6=4.683⇒4.7(nearest tenth)
or
x=(-2-30.1)÷6= -32.1÷6=-5.35⇒ -5.4
Taking the positive value
x=width =4.7 ft
2+3x= length= 2+3(4.7)=16.1 ft
The table shows the number of degrees the temperature increased or decreased over four days. On which day did the temperature change have the greatest magnitude?
Help please the graphs below Have the same shape. What is the equation of the blue graph
Answer:
D. G(x) = (x+2)^2
Step-by-step explanation:
We can easily solve this problem by graphing each case with a graphing calculator or any plotting tool.
The equations are
A. G(x) = (x-2)^2
B. G(x) = (x)^2 + 2
C. G(x) = (x)^2 -2
D. G(x) = (x+2)^2
Se attached image.
The correct option is
D. G(x) = (x+2)^2
Answer:
C. G(x)=x²-2
Step-by-step explanation:
The midpoint of the graph has been displaced from x=0 to x=-2. this is a negative displacement.
Therefore the new equation G(x)=x²-2
This is because there is no tilt in the graph so it is a replica of the red graph.
the equation of a line in the point slope form is show below.
Answer:
A 3
Step-by-step explanation:
y-9 = 3(x-9)
This is in point slope form
y-y1 = m(x-x1)
where (x1,y1) is the point and m is the slope
A point on the line is (9,9) and the slope is 3
Question number 8 please please fast
Answer:
[tex]a_n=-\frac{1}{n}[/tex]
[tex]a_6=-\frac{1}{6}[/tex] is our sixth term.
[tex]a_7=-\frac{1}{7}[/tex] is our seventh term.
[tex]a_8=-\frac{1}{8}[/tex] is our eighth term.
Step-by-step explanation:
So every number in this sequence is -.
If you write 1 as 1/1, then you should see the numerator is constant one while the denominator is going up by 1 each time.
So the patter is
[tex]a_n=-\frac{1}{n}[/tex]
Test if you like:
n=1 gives us [tex]a_1=-\frac{1}{1}=-1[/tex] which is our first term.
n=2 gives us [tex]a_2=-\frac{1}{2}[/tex] which is our second term.
n=3 gives us [tex]a_3=-\frac{1}{3}[/tex] which is our third term.
n=4 gives us [tex]a_4=-\frac{1}{4}[/tex] which is our fourth term.
n=5 gives us [tex]a_5=-\frac{1}{5}[/tex] which is our fifth term.
Now we are going to use [tex]a_n=-\frac{1}{n}[/tex]
to write our next three terms:
n=6 gives us [tex]a_6=-\frac{1}{6}[/tex] which is our sixth term.
n=7 gives us [tex]a_7=-\frac{1}{7}[/tex] which is our seventh term.
n=8 gives us [tex]a_8=-\frac{1}{8}[/tex] which is our eighth term.
f(x)=3x-7 and g(x)=2x-4 find (f+g)(x) and (f-g)(x)
Answer:
(f+g)(x)= 5x-11
(f-g)(x)= x-3
The value of the functions (f + g)(x) and (f - g)(x) will be 5x - 11 and x - 3.
It is required to find the value of (f+g)(x) and (f-g)(x).
What is function?A function is defined as a relation between a set of inputs having one output each. function is a relationship between inputs where each input is related to exactly one output. Every function has a domain and codomain or range. A function is generally denoted by f(x) where x is the input.
Given:
The functions are
f(x) = 3x - 7
g(x) = 2x - 4
We have to find the value of the function (f + g)(x) and (f-g)(x) we get
According to given question we have,
The value of the function (f +g)(x)
(f + g)(x) = f(x) + g(x)
(f + g)(x) = 3x - 7 + 2x - 4
(f + g)(x) = 5x - 11
The value of the function (f - g)(x)
(f - g)(x) = f(x) - g(x)
(f - g)(x) = 3x - 7 - (2x - 4)
(f - g)(x) = 3x - 7 - 2x + 4
(f - g)(x) = x - 3
Therefore, the value of the functions (f + g)(x) and (f - g)(x) will be 5x - 11 and x - 3.
Learn more details about functions here:
https://brainly.com/question/12431044
#SPJ2
Consider the polynomial p(x)=x^3-9x^2+18x-25, which can be rewritten as p(x)=(x-7)(x^2-2x+4)+3. The number blank is the remainder when p(x) is divided by x-7, and so x-7 blank a factor of p(x). Fill in the two blanks with is, 3, 7,is not, or 0!!!!
PLEASE HELP. WILL MARK BRAINLIEST!!
Answer:
[tex]\boxed{\text{3; is not}}[/tex]
Step-by-step explanation:
[tex]\begin{array}{rcl}p(x) & = & (x - 7)(x^{2} - 2x + 4) + 3\\\\\dfrac{p(x)}{x - 7} & = &x^{2} - 2x + 4 + \dfrac{3 }{x-7 }\\\\\end{array}\\\\\text{The number }\boxed{\mathbf{3}}\text{ is the remainder when $p(x)$ is divided by $(x - 7)$,}\\\\\text{so $(x - 7)$ }\boxed{\textbf{is not}} \text{ a factor of $p(x)$.}[/tex]
Solve x - (-9) = -14. -23 23 -5 5
Answer:
-23 = x
Step-by-step explanation:
-(-9) = 9
The thing with double negatives is that they form a plus sign, so that is really a POSITIVE nine. Therefore you do the inverse to find x: -14 - 9 = -23.
I am joyous to assist you anytime.
Answer:
[tex]\Huge \boxed{X=-23}[/tex]
Step-by-step explanation:
[tex]\displaystyle x+9=-14[/tex]
[tex]\Large\textnormal{First, subtract by 9 from both sides of equation.}[/tex]
[tex]\displaystyle x+9-9=-14-9[/tex]
[tex]\Large\textnormal{Simplify, to find the answer.}[/tex]
[tex]\displaystyle -14-9=-23[/tex]
[tex]\Large\textnormal{x=-23, which is our answer.}[/tex]
Find the num
The sum of a number and its reciprocal 10/3. find the number 5
Answer:
x=3 or x= 1/3
Step-by-step explanation:
Let the number = x
The reciprocal of the number = 1/x
According to the given statement:
x+1/x=10/3
x²+1/x=10/3
3(x²+1)=10x
3x²+3=10x
Move 10x to the L.H.S
3x²-10x+3=0
Break the middle term:
3x²-9x-x+3=0
3x(x-3)-1(x-3)=0
(x-3)(3x-1)=0
x-3=0 , 3x-1=0
x=0+3 , 3x=0+1
x=3 , 3x=1
x=3 ,x = 1/3
So x=3 or x= 1/3 ....
The fuel consumption in miles per gallon for a car varies inversely with its weight. Suppose a car that weighs 2800 pounds get 33 miles per gallon on the highway. Write the equation that relates y, the fuel consumption in miles per gallon, to the car's weight, w pounds.
Answer:
y=0.01179/w
Step-by-step explanation:
First understand that the fuel consumption in miles per gallon is inversely proportional to the weight of a car.
If y is the fuel consumption in miles per gallon and w is weight of car in pounds . you can write the first statement as;
y∝1/w
Introduce a constant value for proportionality, k
y=k/w....................make k subject of the formula by multiplying both sides by 1/w
k=y/w
Given in the question that ;
w=2800
y=33
k=?
To find k , apply the formula that you derived above
k=y/w
k=33/2800 =0.011785⇒0.01178(4 significant figures)
Rewrite the formula as
y=k/w ⇒ y=0.01179/w
The equation that relates y and w is;
y=0.01179/w
The fuel consumption in miles per gallon for a car varies inversely with its weight and can be represented mathematically by the inverse proportionality relationship y = k/w. Substituting the given values gives us the constant k = 92400, so the final equation is y = 92400/w.
Explanation:This problem can be defined mathematically by an inverse proportionality relationship, expressed as y = k/w, where k is a constant, y is the fuel consumption in miles per gallon, and w is the weight of the car in pounds.
To find the value of k, we can substitute the given values into the equation. This gives us 33 = k/2800, which simplifies to k = 33 * 2800, or k = 92400.
So, the equation that relates the mileage per gallon, y, to the weight of the car, w, is y = 92400/w. This means the fuel efficiency of a car decreases as its weight increases, thus heavier cars tend to have lower miles per gallon.
Learn more about Inverse Proportionality here:https://brainly.com/question/14437120
#SPJ3
[tex]4c - d - c - 3d[/tex]
[tex]\tt 4c-d-c-3d=3c-4d[/tex]
Answer:
3c -4d
Step-by-step explanation:
4c -d -c -3d
Combine like terms
4c -c -d -3d
3c -4d
What is the solution to the equation below?
log 20х3 - 2logx = 4
x=25
x=50
x=250
x=500
Answer:
x = 500.
Step-by-step explanation:
log20x^3 - 2logx = 4
By the laws of logs:
log20x^3 - logx^2 = 4
log(20x^3 / x^2) = 4
20x^3 / x^2 = 10^4
20x = 10,000
x = 10,000 / 20
x = 500.
The solution of the given logarithmic equation is x = 500.
What is a logarithmic equation?Any equation in the variable x that contains a logarithm is called a logarithmic equation.
Given logarithmic equation
[tex]log20x^{3} -2logx=4[/tex]
Using [tex]mloga=loga^{m}[/tex]
[tex]log20x^{3} -logx^{2}=4[/tex]
Using [tex]loga-logb=log(\frac{a}{b})[/tex]
[tex]\frac{log20x^{3} }{x^{2} }=4[/tex]
[tex]log20x=4[/tex]
[tex]20x=10^{4}[/tex]
[tex]x=\frac{10000}{20}[/tex]
[tex]x=500[/tex]
The solution of the given logarithmic equation is x = 500.
Find out more information about logarithmic equation here
https://brainly.com/question/14411365
#SPJ2
Students observing a caterpillar crawl on a tree noticed that the caterpillar crawled upwards 38 of an inch every minute. The caterpillar was already 4.5 feet off the ground when the students began observing.
Which function represents the total number of inches the caterpillar crawls after x minutes?
f(x) = 4.5x + 3/8
f(x) = 54x + 3/8
f(x( = 3/8x + 54
f(x) = 3/8x + 4.5
Answer:
f(x) = 4.5x + 3/8
Answer: Third Option
[tex]f(x) = \frac{3}{8}x + 54[/tex]
Step-by-step explanation:
We want to propose an equation that models the distance traveled by the caterpillar as a function of time, we have a constant initial quantity of 4.5 feet and then we know that every minute the caterpillar advances 3/8 of an inch
Then the distance that the caterpillar to advanced after x minutes is:
[tex]f(x) = \frac{3}{8}x[/tex]
Then we know that initially the caterpillar was at a distance of 4.5 feet or 54 inch
Then the equation for the distance in inch is:
[tex]f(x) = \frac{3}{8}x + 54[/tex]
6 plus 9 rquals to 10 plus WHAT NUMBER????
Answer: 5.
Step-by-step explanation:
6+9 = 15
10 + x = 15
-10 -10
x = 5
Answer:
x=5
Step-by-step explanation:
6+9=10+x
15=10+x
x=15-10
x=5
simplify. rewrite the expression in the form 9^n:
9^-3/9^12
Answer:
9 ^ (-15)
Step-by-step explanation:
9^-3/9^12
We know that a^b/ a^c = a^(b-c)
9^-3/9^12 = 9 ^(-3-12)
=9^(-15)
The expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
From the question,
we are to rewrite the given expression (9^-3/9^12) in the form 9^n
First, write the expressions properly.
The given expression is
[tex]\frac{9^{-3}}{9^{12} }[/tex]
To rewrite the given expression in the form [tex]9^{n}[/tex], we will use the division law of indices
From the division law of indices, we have that
[tex]x^{y} \div x^{z}= x^{y-z}[/tex]
Then, the given expression becomes
[tex]\frac{9^{-3}}{9^{12} } = 9^{-3} \div 9^{12}[/tex]
[tex]= 9^{-3-12}[/tex]
[tex]=9^{-15}[/tex]
Hence, the expression [tex]\frac{9^{-3}}{9^{12} }[/tex] written in the form [tex]9^{n}[/tex] is [tex]9^{-15}[/tex]
Learn more here: https://brainly.com/question/18205419
Add the two expressions.
−2.4n−3 and −7.8n+2
Enter your answer in the box.
Answer:
-10.2n - 1
Step-by-step explanation:
−2.4n − 3 + (−7.8n + 2) =
= -2.4n - 7.8n - 3 + 2
= -10.2n - 1
Answer:
-10.2n -1
Step-by-step explanation:
−2.4n−3 + −7.8n+2
Combine like terms
−2.4n −7.8n -3+2
-10.2n -1
If f(x) = x^2 + 1 and g(x) = x - 4, which value is equivalent to (fºg)(10)?
Answer:
37
Step-by-step explanation:
Substitute x = 10 into g(x), then substitute the result into f(x)
g(10) = 10 - 4 = 6, then
f(6) = 6² + 1 = 36 + 1 = 37
Find the mean of the data set that consists of 3, 11, 4, 3, 10, 6, 4, 5.
A. 3 and 4
B. 4.5
C. 5.75
D. 5.25
Answer:
5.75
Step-by-step explanation:
[tex]3 + 11 + 4 + 3 + 10 + 6 + 4 + 5 = 46 \\ 46 \div 8 = 5.75[/tex]
The total amount of numbers are : 8
To find the mean, we calculate the sum of all values and divide that sum by the amount of numbers there are.
PLEASE DO MARK ME AS BRAINLIEST IF MY ANSWER IS HELPFUL :)
an engine manufacturer discovered that .05 of a certain production run was defective. What fraction of the run does this represent?
[tex]\huge{\boxed{\frac{1}{20}}}[/tex]
Explanation:To convert from a decimal to a percentage, multiply the decimal by [tex]100[/tex]. [tex]0.05*100=5[/tex], so the percentage equivalent is [tex]5\%[/tex].
Percentages are fractions when you use a denominator of [tex]100[/tex], so [tex]5\%[/tex] is the same as [tex]\frac{5}{100}[/tex]. Divide the numerator and denominator each by [tex]5[/tex] to get the fraction in simplest form, which is [tex]\frac{1}{20}[/tex].
9m=4.5? 3v=-105? 17m=85? please help me:)
please show work:
please show work:
please show work:
thank you
9m = 4.5
divide by 9 for 9m and 4.5
9m/9= 4.5/9
m= 0.5
3v= -105
divide by 3 for 3v and -105
3v/3=- 105/3
v= -35
17m = 85
divide by 17 for 17m and 85
17m/17= 85/17
m= 5
Answers: 0.5,-35 and 5
Triangle HAM is reflected over the y-axis using the rule (x, y) → (−x, y) to create triangle H′A′M′. If a line segment is drawn from point A to point A′, which statement would best describe the line segment drawn in relation to the y-axis?
The line segment drawn from point A to point A′, after reflecting the triangle over the y-axis, is perpendicular to the y-axis. This is because the reflection mirrors the image across the y-axis resulting a right-angle formation between the line segment and the axis.
Explanation:The line segment drawn from point A to point A′, after a reflection of Triangle HAM over the y-axis, would be perpendicular to the y-axis. This is because in a reflection over the y-axis, the x-coordinates of the points change sign and the y-coordinates stay the same. This procedure mirrors the image over the y-axis and creates a segment from A to A′ that is perpendicular to the y-axis and bisects the distance between A and A′.
This idea correlates to the vector concept in physics where components of the vector may be viewed as sides of a right triangle. Much like in that context, the line segment from A to A′ and the y-axis form a right angle, hence they are perpendicular.
Learn more about Reflection over Axis here:https://brainly.com/question/11493726
#SPJ3
Express each ratio as a fraction in lowest terms.
1) 77 to 490
2) 35 to 135
3) 65:1001
Find an equation for the inverse of the function. f(x)=2x-3x/4
Answer:
f⁻¹(x) = (4x)/5
Step-by-step explanation:
f(x) = 2x - 3x/4.
Assume y=f(x). Therefore:
y = 2x - 3x/4.
Make x the subject in the above equation.
y = (2x(4) - 3x)/4.
y = 5x/4.
4y = 5x.
(4y)/5 = x.
x = (4y)/5.
Therefore:
f(y) = (4y)/5.
Replace y with x.
f⁻¹(x) = (4x)/5.
Therefore, the inverse of f(x) = 2x - 3x/4 is f⁻¹(x) = (4x)/5!!!
A: What are the solutions to the quadratic equation?
B: which statements accurately interpret the solution?
Answer:
A. x = -1 or x = 3B. firstStep-by-step explanation:
[tex]x^2-2x-3=0\\\\x^2+x-3x-3=0\\\\x(x+1)-3(x+1)=0\\\\(x+1)(x-3)=0\iff x+1=0\ \vee\ x-3=0\\\\x+1=0\qquad\text{subtract 1 from both sides}\\x=-1\\\\x-3=0\qquad\text{add 3 to both sides}\\x=3[/tex]
Which are correct representations of the inequality –3(2x – 5) < 5(2 – x)? Check all that apply.
x < 5
–6x – 5 < 10 – x
–6x + 15 < 10 – 5x
Answer:
[tex]-6x+15< 10-5x[/tex]
Step-by-step explanation:
we have
[tex]-3(2x-5) < 5(2-x)[/tex]
solve for x
eliminate the parenthesis (apply the distributive property)
[tex]-3*2x+3*5 < 5*2-5*x[/tex]
[tex]-6x+15< 10-5x[/tex] ---> correct representation of the inequality
Adds (5x-15) both sides
[tex]-6x+15+5x-15< 10-5x+5x-15[/tex]
[tex]-x< -5[/tex]
Multiply by -1 both sides
[tex]x>5[/tex]
If triangle DEC congruent to triangle BEC, which is true by CPCTC?
Answer:
The correct answer is the second one
Step-by-step explanation:
Line BE and ED are congruent because they are the same length and E is the mid line.
Answer:
second option is correct
Step-by-step explanation:
By the given
ΔDEC≅ΔBEC
which means triangle DEC is congruent to triangle BEC
then by CPCTC (corresponding parts of congruent triangle are congruent)
there every side and angle of DEC will be equal to BEC
⇒BE= DE (by CPCTC)
hence second option is correct
40 POINTS!!!!
graph the function g(x) = x3 − x2 − 4x + 4. (an actual graph that you can attach)
Answer:
see below
Step-by-step explanation:
g(x) = x^3 − x^2 − 4x + 4
We know the graph will have up to 3 zero's because it is a cubic
g(x) = x^3 − x^2 − 4^x + 4
I will factor by grouping, taking an x^2 from the first 2 terms and -4 from the last 2 terms
g(x)= x^2(x-1) -4(x-1)
Now factor out x-1
g(x)= (x-1)(x^2 -4)
We can factor the (x^2-4) as a difference of squares
g(x) = (x-1) (x-2)(x+2)
Using the zero product property
0= (x-1) (x-2)(x+2)
x-1 =0 x-2 =0 x+2=0
We have zeros at x=1 x=2 and x=-2
Then we can plot points to determine where the function is between the points We will pick negative infinity 0 1.5 and infinity
at g(-inf) = -inf because x^3 dominates and that goes to -infinity
at g(0) = 0+000+4 =4
at g(1.5) =-.875
at g(inf)=because x^3 dominates and that goes to infinity
how much must you deposit in an account that pays 6.25% interest compounded annually to have a balance of $700 after 2 years
Answer:
[tex]\$620.07[/tex]
Step-by-step explanation:
we know that
The compound interest formula is equal to
[tex]A=P(1+\frac{r}{n})^{nt}[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
[tex]t=2\ years\\A=\$700\\ r=0.0625\\n=1[/tex]
substitute in the formula above and solve for P
[tex]700=P*(1+\frac{0.0625}{1})^{2}[/tex]
[tex]700=P*(1.0625)^{2}[/tex]
[tex]P=700/(1.0625)^{2}[/tex]
[tex]P=\$620.07[/tex]
Do you prefer to express solutions to inequalities using interval notation or as an inequality? Do you think it is important to know both formats? How could each be used?
Answer:
I prefer to express solutions to inequalities using interval notation. Both formats are are important but I think interval notation is easier to understand and represents better the solutions.
For example, if you have the following inequation:
x-2> 1
x>3
Therefore, the solution could be written either x>3 OR (3, +inf). But what happens if the solution to the system of equation is x>3 or x<-3? The solution can be easily written as: (-inf, -3) U (3, inf) instead of 'x>3 or x<-3' which can be confusing.
To express solutions to inequalities using interval notation.
I prefer to express solutions to inequalities using interval notation. Both formats are important but I think interval notation is easier to understand and represents better the solutions.
For example, if you have the following inequation:
x-2> 1
x>3
Therefore, the solution could be written either x>3 OR (3, +inf). But what happens if the solution to the system of equation is x>3 or x<-3? The solution can be easily written as: (-inf, -3) U (3, inf) instead of 'x>3 or x<-3' which can be confusing.
Hence, To express solutions to inequalities using interval notation.
Learn more about interval notations here https://brainly.com/question/18586505
#SPJ2